2021
DOI: 10.2147/ijn.s294916
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Nanomicelles Target Neuroinflammation and Improve Neurological Deficit in a Mouse Model of Intracerebral Hemorrhage

Abstract: Background: Intracerebral hemorrhage (ICH), a devastating subtype of stroke, has a poor prognosis. However, there is no effective therapy currently available due to its complex pathological progression, in which neuroinflammation plays a pivotal role in secondary brain injury. In this work, the use of statin-loaded nanomicelles to target the neuroinflammation and improve the efficacy was studied in a mouse model of ICH. Methods: Rosuvastatin-loaded nanomicelles were prepared by a co-solvent evaporation method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…In their study examining the effects of simvastatin in a rat model of intracerebral haemorrhage, statin treatment was seen to upregulate CD36 expression as well as increasing PPARγ activation, facilitating M2-like phenotype polarization in perihematomal microglia [164]. Similarly, rosuvastatin-loaded nanomicelles were found to stimulate microglia/macrophages to an M2 phenotype in a mouse model of intracerebral haemorrhage, where they also reported reduced tissue levels of IL-1β and TNFα and increased levels of IL-10 [165]. Various other studies in a range of rodent models have also reported atorvastatin and pravastatin to have macrophage-polarizing actions, demonstrated by augmented M1/M2 ratios [103,[166][167][168].…”
Section: In Vivo Studies Investigating the Effects Of Statins On Macr...mentioning
confidence: 95%
“…In their study examining the effects of simvastatin in a rat model of intracerebral haemorrhage, statin treatment was seen to upregulate CD36 expression as well as increasing PPARγ activation, facilitating M2-like phenotype polarization in perihematomal microglia [164]. Similarly, rosuvastatin-loaded nanomicelles were found to stimulate microglia/macrophages to an M2 phenotype in a mouse model of intracerebral haemorrhage, where they also reported reduced tissue levels of IL-1β and TNFα and increased levels of IL-10 [165]. Various other studies in a range of rodent models have also reported atorvastatin and pravastatin to have macrophage-polarizing actions, demonstrated by augmented M1/M2 ratios [103,[166][167][168].…”
Section: In Vivo Studies Investigating the Effects Of Statins On Macr...mentioning
confidence: 95%
“…The multifaceted effects of statins may reduce brain damage in patients after ICH and improve their prognosis. Several animal studies have shown that statins have many neuroprotective effects, including protection of the blood-brain barrier (BBB), inhibition of inflammatory cytokines, anti-apoptotic effect, and reduction of brain edema after ICH [92][93][94][95][96]. Although the evidence for statin use in ICH remains unclear, the risks of their use have been low, and there is no need to avoid their use intensively.…”
Section: Intracerebral Hemorrhagementioning
confidence: 99%
“…Polymer-based nanomaterials are used for neuroprotection by optimizing pharmacological properties or improving the site-specific delivery of neuroprotectants and genes including resveratrol (Res), curcumin, rosuvastatin, dauricine (DRC), astaxanthin (ATX), neurotrophin-3 (NT-3). [45][46][47][48][49][50][51] Polymer-based nanomaterials with ROS scavenging and iron chelation properties are also used for neuroprotection of hemorrhagic stroke. 52,53 Polymer-based nanomaterials prevented complications after SAH by improving targeted delivery of the calcitonin gene-related peptide (CGRP) gene.…”
Section: Polymer-based Nanomaterialsmentioning
confidence: 99%